Investigating the Relationship Between Individual Innovativeness and Programming Anxiety - Melih Engin (Üniversite Araştırmaları Dergisi)
This study investigates the levels of anxiety among university students regarding programming and examines the factors influencing this anxiety. The research explores the relationships between students’ characteristics such as, risk-taking, leadership qualities, openness to experience, and resistance to change with their programming anxiety. The study’s participants were 427 university students who had undergone programming education prior to 2023. Individual innovativeness and programming concerns of the research participants were analyzed primarily with descriptive statistical methods. Afterwards, the relationships between the sub-dimensions of individual innovativeness and levels of programming anxiety were investigated using relational screening models. Results indicate a slight positive correlation between reluctance towards change and receptiveness to new experiences with programming anxiety, whereas a modest negative correlation is observed between willingness to take risks and leadership qualities. The combination of these factors moderately and significantly predicts students’ levels of programming anxiety. The research offers valuable perspectives for educators and developers of programs seeking to create methods to ease the anxiety students face in programming education.